The Bitcoin Standard Applied to Brazil: a Suggestion of Monetary Policy and a Review of the function of the Central Bank - Fiuza, Lucas (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2019)
The purpose of this paper is to make a simplified suggestion to change the Brazilian monetary policy and review the role of the Central Bank. The author uses, as main pillar, a digital asset developed with a unique combination of technologies: Bitcoin, whose functionality infrastructure is decentralized. Also, its transaction record is immutable and public; it can be transferred between parties globally without intermediaries; and its issuance is limited, making it truly scarce. To formulate this suggestion, it was necessary to create hypotheses based on the historical value of Bitcoin and its adoption by the market, while aware that such hypotheses are strictly conjectures of possible scenarios, although absolutely unpredictable. The idea is so recent that only the imagination can give us visions of the future regarding the use and development of this new technology.